2020
DOI: 10.1177/1120700019897878
|View full text |Cite
|
Sign up to set email alerts
|

Blood transfusion rates and predictors following geriatric hip fracture surgery

Abstract: Background: Postoperative blood product transfusions in elderly hip fracture patients cause concern for morbidity and mortality. The purpose of this study was to identify predictors and short-term sequelae of postoperative transfusion following geriatric hip fracture surgery. Methods: We queried the American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) to identify geriatric (⩾65 years) patients who sustained operative femoral neck, intertrochanteric, and subtrochanteric hip fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
54
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 35 publications
13
54
1
5
Order By: Relevance
“…These risk factors associated with the poor prognosis after hip fracture has been confirmed in the previous studies [30,31]. Although blood transfusion was associated with mortality after hip fracture in some studies [32,33], no such relationship was found in our data. We speculated that the possible reason was that the number of patients receiving blood transfusion were small (n = 84 in our study), which may influence this relationship.…”
Section: Discussionsupporting
confidence: 86%
“…These risk factors associated with the poor prognosis after hip fracture has been confirmed in the previous studies [30,31]. Although blood transfusion was associated with mortality after hip fracture in some studies [32,33], no such relationship was found in our data. We speculated that the possible reason was that the number of patients receiving blood transfusion were small (n = 84 in our study), which may influence this relationship.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, the preoperative Hb of the blood transfusion group was (113.9 ± 14.0) g/L, which was signi cantly lower than the preoperative Hb (128.2 ± 12.8) g/L of the non-transfusion group (p < 0.05). This result is consistent with many previous studies [7,9,13] . Adunsky A et al [14] found that patients with preoperative Hb lower than 120 g/L have a 5-fold increase in the risk of postoperative blood transfusion.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, the preoperative Hb of the blood transfusion group was (113.18 ± 14.69) g/L, which was signi cantly lower than the preoperative Hb (128.80 ± 12.41) g/L of the nontransfusion group (p < 0.05). This result is consistent with many previous studies [7,9,13] . Adunsky A et al [14] found that patients with preoperative Hb lower than 120 g/L have a 5-fold increase in the risk of postoperative blood transfusion.…”
Section: Discussionsupporting
confidence: 94%
“…Consistent with previous studies [7,13] , we found that advanced age is an independent risk factor for ABT in elderly FNF patients after HA. This may be related to the lower baseline Hb of older people.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation